Ethical Violations of Nursing Students in Field Practice: Analysis 0f Causal Factors and Prevention Strategies - Francois Villon Putra Maleakhi; Antonius Hendra Irawan; Julian Putra Pangaribuan; Yoseph Waltrudis Carol (PT. Caesarindo Triloka Persada, 2025)
Field practice is an important component of nursing education that allows students to apply theory in real clinical situations. However, various ethical violations often occur during this period, raising concerns for the quality of education and patient safety. This study aims to identify the types of ethical violations committed by nursing students, analyze the causative factors, and formulate effective prevention strategies. The research method used was descriptive qualitative with a case study approach. Data were collected through in-depth interviews with 30 nursing students, 15 clinical supervisors, and 10 heads of rooms from various hospitals in the East Java region. The results showed that the most frequent ethical violations included violations of patient privacy (78%), dishonesty in documentation (65%), and violations of safety procedures (52%). The main causative factors included lack of understanding of ethics, academic pressure, and lack of supervision. Recommended prevention strategies include strengthening ethics education, improving supervision systems, and developing comprehensive ethics guidelines.